PBA ; General Alfredo Lim ; Bilmoko [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
The controversial issue of game fixing in basketball ; A profile of the fearless general of the Manila Western Police District. A San Miguel beer advertisement stirs a hornet's nest and the song of Fred Panopio that talks about women whose every whim is granted.
PBA (22 min.) -- General Alfredo Lim (9 min.) -- Bilmoko (16 min.)
VHS
Keywords: Lim, Alfredo Siojo -- Interviews; Philippine Basketball Associatio. Officials and employees; Advertisements -- Philippines; Basketball -- Philippines